An Escalade, a Briefcase, and Respect: Latinx Youth’s Imaginings of Middle-Class Status and a Cosmopolitan Good Life in Nashville, Tennessee - Flores, Andrea (Anthropologica, 2024)
Latinx immigrant-origin youth in Nashville, Tennessee—who are poised to be the first in their families to achieve middle-class status—strive toward a cosmopolitan future of professional work and disposable income. This social and economic mobility is imagined in relation to the racialization and stigmatization of Latinx people as exclusively working-class labourers and as the objects of a Southern, white cosmopolitan gaze. Through their aspirations, youth challenge existing local and global regimes of labour, consumption, and difference. With respect to work, youth seek to remake the white professional world in ways specific to their Latinx experience. In so doing, they reclaim the value of Latinx labour. They also look to engage in specific kinds of material accumulation that, while leading to tangibly more comfortable lives individually, also make their worth visible to others. Finally, youth’s views of a future defined by their ability to cross cultures and borders repositions their ethno-racial and linguistic difference as an asset rather than a liability. Moreover, this global orientation reorients cosmopolitanism away from a position of exclusively white and elite status. Collectively, these imaginings reveal that while middle-class aspirations may reinforce a colour line of class, they also potentially remake existing racialized hierarchies of class, mobility, and cosmopolitanism.